2010
DOI: 10.3899/jrheum.091116
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Artery Endothelial-dependent Flow-mediated Dilation Identifies Early-stage Endothelial Dysfunction in Systemic Sclerosis and Correlates with Nailfold Microvascular Impairment

Abstract: We demonstrated the simultaneous presence of macrovascular and microvascular impairment in patients with SSc, which was already present in the early phase of the vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 24 publications
5
37
0
1
Order By: Relevance
“…Another study showed that flowmediated dilatation was decreased in patients with SSc compared with controls (8). Some studies found nitratemediated dilatation was reduced in SSc, suggesting coexisting functional or structural abnormalities of arterial smooth muscle, adventitia, or both (48,49). Our patient cohort had an impaired CFR with increased ADMA levels.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Another study showed that flowmediated dilatation was decreased in patients with SSc compared with controls (8). Some studies found nitratemediated dilatation was reduced in SSc, suggesting coexisting functional or structural abnormalities of arterial smooth muscle, adventitia, or both (48,49). Our patient cohort had an impaired CFR with increased ADMA levels.…”
Section: Discussionmentioning
confidence: 81%
“…Among the noninvasive techniques, echocardiography with CFR assessment plays the most important role, as has been reported in a recent review undertaken by the University of California (46). However, endothelial dysfunction has been assessed using flow-mediated dilatation (47,48). Another study showed that flowmediated dilatation was decreased in patients with SSc compared with controls (8).…”
Section: Discussionmentioning
confidence: 96%
“…Since calcification and fibrosis reduce vascular compliance and subsequently affect NO signaling by limiting vascular stretch [72,73], vascular stiffness itself is also an important factor determining FMD. In SSc patients, several studies have demonstrated the reduction of FMD values [74][75][76][77][78][79][80][81]. More importantly, the inverse correlation of FMD values with pulmonary arterial pressure and the association of decreased FMD values with the presence of PAH and digital ulcers have been reported [12,79].…”
Section: Endothelial Dysfunction In Sscmentioning
confidence: 96%
“…The increase observed in the BA diameter is an indirect measure of NO release, and, thus, of endothelium-dependent vasodilation. 15 A small percentage fl ow increase mediated by endotheliumdependent vasodilation can be interpreted as low availability of NO, being associated with an increased risk for vascular disease. 16 The defi cient endothelium-dependent vasodilation found in SSc can be explained by lack of production and release of vasodilating substances by the chronically injured endothelium, especially NO, while normal vasodilating response to endothelium-independent factors (exogenous nitroglycerin) can be observed.…”
Section: Introductionmentioning
confidence: 99%